2022
DOI: 10.1002/advs.202200374
|View full text |Cite
|
Sign up to set email alerts
|

Through‐Space Conjugated Electron Transport Materials for Improving Efficiency and Lifetime of Organic Light‐Emitting Diodes

Abstract: Thermally stable electron transport (ET) materials with high electron mobility and high triplet state energy level are highly desired for the fabrication of efficient and stable organic light‐emitting diodes (OLEDs). Herein, a new design strategy of constructing through‐space conjugated folded configuration is proposed to explore robust ET materials, opposite to the widely used planar configuration. By bonding two quinolines to the 9,10‐positions of phenanthrene, two novel folded molecules with high thermal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 65 publications
(42 reference statements)
1
20
0
Order By: Relevance
“…The π...π interactions in Cb-3-GY have exhibited two scenarios, the local π...π interaction in the distance of 3.23 Å with an overlapping ratio of 3% and the through-space conjugation in an average distance of 3.75 Å (Figure 4f). 45,46 The key factor in determining such an uncommon crystallography rested with a slight change in the dihedral angle between DBT and phenylethyne, which was 89.7°and 92.4°for the successive through-space conjugation, and 73.3°f or the local π...π interactions. Therefore, it could be inferred that THF prompted the rotation of DBT and induced different crystallography compared with benzene, even though it was not co-crystallized in Cb-3-GY.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The π...π interactions in Cb-3-GY have exhibited two scenarios, the local π...π interaction in the distance of 3.23 Å with an overlapping ratio of 3% and the through-space conjugation in an average distance of 3.75 Å (Figure 4f). 45,46 The key factor in determining such an uncommon crystallography rested with a slight change in the dihedral angle between DBT and phenylethyne, which was 89.7°and 92.4°for the successive through-space conjugation, and 73.3°f or the local π...π interactions. Therefore, it could be inferred that THF prompted the rotation of DBT and induced different crystallography compared with benzene, even though it was not co-crystallized in Cb-3-GY.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A breakthrough in the development of a single molecule with TSCT properties occurred in 2017 when Swager and co-workers [30] linked D and A by a bridging group to obtain U-shaped molecules that exhibited AIEE, mechanochromism and TADF properties. Single crystal structures of XPT (32), XCT (33), and XtBuCT (34) showed that D and A were arranged in a cofacial arrangement with D-A distances of 3.3-3.5 Å (Figure 4d). In nitrogen atmosphere, the materials exhibited two-component fluorescence, which included a distinctive delayed (τ d ) 2.3 μs relaxation and a prompt (τ p ) 2.8 ns relaxation (XPT (32)), in consistency with the prompt and delayed emissive characteristics of TADF systems (Figure 4e).…”
Section: Other Bridged Tadf Emittersmentioning
confidence: 99%
“…Copyright 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. d) Single-crystal structures of XPT(32), XCT(33), and XtBuCT(34), from left to right. e) PL transient spectrum of XPT(32) in toluene (1 × 10 À 4 M, λ ex = 336 nm) under saturated oxygen and saturated nitrogen at room temperature.…”
mentioning
confidence: 99%
“…Last but not the least, due to its large π-conjugation and rigid structure, the PI derivatives usually possess high thermal stability, and more importantly, regular aggregation and nice carrier transportation properties can also be expected. [27,46,47] In this work, a relatively weak acceptor unit benzoxazole is chosen and a novel D-A blue emissive material 2-(4″-(1-phenyl-1H-phenanthro [9,10-d]imidazol-2-yl)-[1,1″-biphenyl]-4-yl) benzo [d]oxazole (PPIPBO) was successfully synthesized and characterized. PPIPBO showed typical HLCT character, contributing to the high quantum efficiency (ϕ PL ) of 80.6% in neat film.…”
Section: Introductionmentioning
confidence: 99%